Ultra-high-Q thin-silicon nitride strip-loaded ring resonators - Stefan, L; Bernard, M; Guider, R; Pucker, G; Pavesi, L; Ghulinyan, M (Optics letters, 2015)
We report on the design, fabrication, and characterization of thin Si3N4 ultra-high-quality (UHQ) factor ring resonators monolithically integrated on a silicon chip. The devices are based on a strip-loaded configuration and operate at both near-infrared (NIR) and third-telecom wavelengths. This approach allows us to use a guiding Si3N4 core that is one order of magnitude thinner than what has been reported in the past for obtaining similar device performances. Our strip-loaded devices benefit from the absence of physically etched lateral boundaries to show minute light scattering and, therefore, reducing significantly scattering-related losses. Consequently, UHQs of 3.7×10(6) in the NIR and high-quality factors of up to 9×10(5) in the C-band were measured for the guiding material thickness of 80 nm and 115 nm, respectively. These first results are subject to further improvements that may allow employing strip-loaded resonators in nonlinear frequency conversion or quantum computing schemes within the desired spectral range provided by the material transparency.